2019
DOI: 10.1021/acs.molpharmaceut.9b00586
|View full text |Cite
|
Sign up to set email alerts
|

Activation of Angiogenesis and Wound Healing in Diabetic Mice Using NO-Delivery Dinitrosyl Iron Complexes

Abstract: In diabetes, abnormal angiogenesis due to hyperglycemia and endothelial dysfunction impairs wound healing and results in high risks of diabetic foot ulcers and mortality. Alternative therapeutic methods were attempted to prevent diabetic complications through the activation of endothelial nitric oxide synthase. In this study, direct application of nitric oxide using dinitrosyl iron complexes (DNICs) to promote angiogenesis and wound healing under physiological conditions and in diabetic mice is investigated. B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
51
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(52 citation statements)
references
References 50 publications
1
51
0
Order By: Relevance
“…Lin et al used emulsion technique to prepare NaHS particles (NaHS@MPs), which could be used as in situ depot for continuous release of exogenous H 2 S under physiological conditions. 197 The sustained release of H 2 S from NaHS@MPs promotes several cell behaviors, including epidermal/endothelial cell proliferation and migration, as well as angiogenesis, by extending the activation of cellular ERK1/2 and p38, [181,[192][193][194] Sodium percarbonate PCL nanofibers scaffolds Continuously generating oxygen for up to 10 days [190] Sodium hydrosulfide NaHS@MPs NaHS@MPs sustained release of exogen-ous H2S under physiological conditions [197] Nitric oxide DNICs Continuous release of nitric oxide [201] submit your manuscript | www.dovepress.com…”
Section: Hydrogen Sulfide Containing Nanocarriersmentioning
confidence: 99%
See 1 more Smart Citation
“…Lin et al used emulsion technique to prepare NaHS particles (NaHS@MPs), which could be used as in situ depot for continuous release of exogenous H 2 S under physiological conditions. 197 The sustained release of H 2 S from NaHS@MPs promotes several cell behaviors, including epidermal/endothelial cell proliferation and migration, as well as angiogenesis, by extending the activation of cellular ERK1/2 and p38, [181,[192][193][194] Sodium percarbonate PCL nanofibers scaffolds Continuously generating oxygen for up to 10 days [190] Sodium hydrosulfide NaHS@MPs NaHS@MPs sustained release of exogen-ous H2S under physiological conditions [197] Nitric oxide DNICs Continuous release of nitric oxide [201] submit your manuscript | www.dovepress.com…”
Section: Hydrogen Sulfide Containing Nanocarriersmentioning
confidence: 99%
“…Chen et al activated the NO-sGC-cGMP pathway by inducing long-term NO release ( t = 27.4±0.5 h at 25°C and 16.8±1.8 h at 37°C) and maintaining the angiogenesis process. 201 …”
Section: Substances Applied In Diabetic Wound Healingmentioning
confidence: 99%
“…In this study, we reported that HGWWD treatment significantly restored aortic vascular endothelial dysfunction through NO signaling (Figure 3). Abnormal NO levels have been reported in vascular pathological conditions (Bondonno et al, 2016), and intervention in NO signaling can effectively prevent various vascular disorders, including endothelial dysfunction, vascular inflammation and vascular stiffness (Bondonno et al, 2016;Batko et al, 2019;Chen et al, 2019). Furthermore, excessive arginase activation can down-regulate NO production by reducing NOS availability through competition for their common substrate L-arginine (Bhatta et al, 2017;Zhou et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…As a potential biological equivalent of NO, bioinorganic engineering of [Fe(NO) 2 ] unit has emerged to develop biomimetic DNICs as a chemical biology tool for controlled delivery of NO and translation of NO-related functions into biomedical applications [23,24]. In particular, biomimetic DNICs and their conjugates with drug delivery systems were explored for antiaging/anti-inflammatory/anti-viral effect, anti-cancer/anti-hypertensive therapy, diabetic angiogenesis/wound healing, penile erection, and treatment of mild cognitive impairment and neurodegenerative diseases [25][26][27][28][29][30][31][32][33][34][35]. In particular, phase I and phase II clinical trials of glutathione-bound DNICs [Fe 2 (µ-glutathione) 2 (NO) 4 ], a commercial medical product with the pharmacological name Oxacom ® , was reported for application as a clinical medicine against hypertension [30,31].…”
Section: Introductionmentioning
confidence: 99%
“…Inspired by the potential of biomimetic DNICs for biomedical applications, synthetic advances in the development of structure-characterized and water-soluble DNICs enabled the study of trafficking and NO-delivery reactivity of DNICs under simulated physiological conditions, in vitro, and in vivo [26,28,[36][37][38][39]. Water-soluble DNIC [Fe 2 (µ-SCH 2 CH 2 OH) 2 (NO) 4 ] (DNIC-1) displays an O 2 -triggered degradation mechanism for the release of nitric oxide, ferric ion, and disulfide with a half-life of 27.4 h and 15.5 h in an aqueous buffer solution (pH = 7.0 or 7.4) at 25 • C and 37 • C, respectively [25,32,34]. In simulated gastric fluid (SGFsp, pH 1.2), a shortened half-life of 0.4 h indicates the acid-sensitive nature of DNIC-1.…”
Section: Introductionmentioning
confidence: 99%